Flow and instability of liquid compound jets - Radev, Stefan (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
A review of the current state of the fluid mechanics of compound jets is presented. The mentioned jet configuration originates from the paper of Hertz & Hermanrude [21], in which the first observations of the behaviour of the flow and instability of a compound jet were reported. The following aspects of the compound jet hydrodynamics are summarized in this review: (i) flow models, (ii) steady state flow, (iii) small disturbances instability of a compound jet - a linear approximation, (iv) propagation of finite amplitude perturbations - a weakly nonlinear approximation, (v) direct numerical simulation of the disintegration of a compound jet, (vi) asymmetrical instability in linear approximation.